AISYIYAH: Its Role and Dynamics in the Development of Education in Palopo City - Duriani Sirajuddin (Universitas Muhammadiyah Enrekang, 2023)
This research aims to provide a general overview of the role and dynamics of the development of Aisyiyah education in Palopo City in achieving an intelligent and moral Karimah generation. This research looks at the performance of Aisyiyah Bustanul Athfal I Kindergarten, Aisyiyah Bustanul Athfal II Kindergarten, Aisyiyah Bustanul Athfal II Peta Kindergarten, Aisyiyah Bustanul Athfal IV, Bara Palopo District, starting from curriculum planning, learning, to implementation. The research uses a qualitative approach with descriptive methods to obtain more accurate information. Data collection techniques through observation, documentation and interviews, then analyzed using data reduction steps, data presentation and drawing conclusions. The results of the research show that of the four Aisyiyah kindergartens in Palopo City, all of them use a curriculum in accordance with PAUD standards using thematic learning with a scientific approach, and prepare learning plans by making semester programs in advance, Weekly Learning Implementation Plans, Daily learning and assessment as a process of measuring the results of children's learning activities.